Probiotic potential and antimicrobial effects of lactic acid bacteria isolated from palm wine against foodborne pathogens in Ghana - Nana Kwabena Oduro Darko; Felix Charles Mills-Robertson (Food Chemistry Advances)
Beyond being a traditional beverage, palm wine is a rich source of lactic acid bacteria (LAB) with potential applications as starter cultures in the food and feed industries. While LAB is commonly isolated from the gastrointestinal tract, externally sourced strains may offer similar probiotic benefits. This study investigated the probiotic potential of LAB isolated from palm wine through in vitro assessments. Two LAB strains were isolated through pour plating and identified via MALDI TOF MS. Their ability to survive acidic conditions and varying bile concentration was evaluated. Additionally, their antimicrobial activity against food borne pathogens was assessed via disc diffusion. The identified strains; L. mesenteroides and L. fermentum remained viable in low acidic conditions but showed a decline in viability after 4 h, indicating acid stress. Both strains tolerated bile salts though their numbers decreased from 783 to 486 CFU/ml with increased bile salt concentration. Both isolates exhibited antimicrobial activity against E.coli, E. faecalis, P. aeruginosa and E. cloacae with inhibition zones ranging from 7 -14 mm. This study opens new avenues for sourcing probiotics from natural and unconventional sources like palm wine. The LAB strains identified in this research present themselves as promising subjects for further investigation. Subsequent studies should focus on improving strain robustness, cost-effective stabilization methods and in vivo validation to support their industrial and health applications.